Impact of Pacemaker Implantation on 12-Month Resource Utilization Following TAVR Hospitalization - Culler, Steven D; Kugelmass, Aaron D; Cohen, David J; Reynolds, Matthew R; Brown, Phillip P; Simon, April W; Katz, Marc R (Journal of Cardiology and Cardiovascular Medicine, 2019)
Purpose: This study reports resource utilization during a Medicare Beneficiary’s (MBs) Transcatheter Aortic Valve Replacement (TAVR) index hospitalization and all subsequent encounters for 12 months and compares data between MBs who did or did not receive a pacemaker implantation (PPM) during their index hospitalization. Method: This retrospective study examined Medicare hospital claims from January 1, 2014 through June 30, 2015. 15,533 MBs who survived for 365 days were studied. Information from all encounters during the study period was combined to compare hospital resource utilization and outcomes. Results: 14.8% of MBs had a PPM during the index hospitalization. 46.0% of MBs had at least one readmission to a hospital during the 365-day follow-up period. 54.6% of MB’s first hospital readmission occurred within 90 days of their TAVR discharge date. Average total Medicare reimbursement for all hospitalizations was $60,638 ± $28,974 associated with average total hospital length of stay of 11.2 ± 11.7 days. After adjusting for demographics and 47 comorbid conditions, MBs receiving a PPM during the index TAVR had significantly higher estimated Medicare reimbursement ($5,132) and longer total length of stay (1.8 days) for the entire study period than MBs not receiving a PPM. Conclusion: Total Medicare reimbursement and hospital LOS were significantly higher among MBs that had a PPM implantation during their index admission; however, there were no significant differences in readmission rates, readmission length of stay, or days to first readmission during the follow-up period between the two study cohorts.